2016
DOI: 10.1016/j.spinee.2016.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of spinal manipulative therapy, supervised exercise, and home exercise for older adults with chronic neck pain

Abstract: Background Context Chronic neck pain is a prevalent and disabling condition among older adults. Despite the large burden of neck pain, little is known regarding the cost-effectiveness of commonly used treatments. Purpose To estimate the cost-effectiveness of home exercise and advice (HEA), spinal manipulative therapy (SMT) plus HEA, and supervised rehabilitative exercise (SRE) plus HEA. Study Design/Setting Cost-effectiveness analysis conducted alongside a randomized clinical trial (RCT). Patient Sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 63 publications
(64 reference statements)
1
24
0
1
Order By: Relevance
“…The observed reduction of medical interventions usage suggested that the AI system might have additional cost saving benefit. This finding was supported by a cost effectiveness study published Leininger et al, (2016) [1].…”
Section: Needs For Other Interventionssupporting
confidence: 56%
See 2 more Smart Citations
“…The observed reduction of medical interventions usage suggested that the AI system might have additional cost saving benefit. This finding was supported by a cost effectiveness study published Leininger et al, (2016) [1].…”
Section: Needs For Other Interventionssupporting
confidence: 56%
“…Chronic musculoskeletal neck and back pain are prevalent and disabling conditions among adults [1]. The studies published in 2010 on the global economic burden of disease indicated low back pain and neck pain ranked sixth and twenty-first respectively out of 291 diseases and injuries [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exercise therapy was associated with higher costs and smaller effects than home exercise alone 36. The incremental cost-utility ratio value was not reported 36…”
Section: Cost-effectiveness Of Exercise Therapymentioning
confidence: 99%
“…Can we all admit that the correct treatment is the one that gives the patient the most benefit and the least harm? There is evidence that including manual therapy care as part of the conservative management of patients with musculoskeletal conditions results in cost effective improvements in pain, function and satisfaction [5][6][7]. Objectively measuring clinical reasoning is a difficult task and 5 'expert' clinicians may use 5 different approaches to achieve a favorable outcome.…”
Section: We Need To Debate the Value Of Manipulative Therapy And Recomentioning
confidence: 99%